2010
DOI: 10.1063/1.3489091
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting plasmonics and extraordinary transmission

Abstract: Negative dielectric constant and dominant kinetic resistance make superconductors an intriguing plasmonic media. Here we report on the first study of one of the most important and disputed manifestations of plasmonics, the effect of extraordinary transmission through an array of subwavelength holes, using a perforated film of high-temperature superconductor.The effect of extraordinary transmission can be regarded as one of the most important and disputable phenomenon in the area of plasmonics. It was observed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…This is also reflected by the negligible imaginary part of the complex dielectric constant compare to the real part, which is negative. Therefore we argue that coupled excitations much like optical plasmons in metals should exist in the superconductors at frequencies that fall in the superconducting gap.Our previous experiments on extraordinary transmission through perforated superconducting films have indirectly shown the existence of the superconducting plasmons, which were held responsible for the enhancement of the effect upon superconducting transition [1]. Here we present the first direct evidence of highly localised plasmonic TM-modes supported by high-T c superconducting gap-and groove-waveguides of sub-micrometre lateral dimensions.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…This is also reflected by the negligible imaginary part of the complex dielectric constant compare to the real part, which is negative. Therefore we argue that coupled excitations much like optical plasmons in metals should exist in the superconductors at frequencies that fall in the superconducting gap.Our previous experiments on extraordinary transmission through perforated superconducting films have indirectly shown the existence of the superconducting plasmons, which were held responsible for the enhancement of the effect upon superconducting transition [1]. Here we present the first direct evidence of highly localised plasmonic TM-modes supported by high-T c superconducting gap-and groove-waveguides of sub-micrometre lateral dimensions.…”
mentioning
confidence: 55%
“…Our previous experiments on extraordinary transmission through perforated superconducting films have indirectly shown the existence of the superconducting plasmons, which were held responsible for the enhancement of the effect upon superconducting transition [1]. Here we present the first direct evidence of highly localised plasmonic TM-modes supported by high-T c superconducting gap-and groove-waveguides of sub-micrometre lateral dimensions.…”
mentioning
confidence: 55%
“…The main focus of metamaterial research today is in developing new switchable and active media, predominantly through hybridizing metamaterial arrays with other functional materials [1]. Compared to the conventional metamaterials made using metallic resonators [2], the metamaterials fabricated from superconductors posses unique advantages that are linked to low Joule losses in the microwave and terahertz spectral ranges [3][4][5]. However, the most important advantages of the superconducting metamaterials are related to the nature of superconductivity.…”
mentioning
confidence: 99%
“…For instance, the macroscopic quantum state of the supercon-ducting charge carriers makes superconducting metamaterials extremely sensitive to many external stimuli allowing quantum level nonlinearities with arrays containing Josephson Junctions [6][7][8][9][10][11][12], and with metamaterials exploiting the recently introduced quantum flux exclusion mechanism of nonlinearity [13]. Over the last decade researchers have demonstrated that light [14], magnetic field [15][16][17], and temperature [5,16,[18][19][20][21][22][23][24][25][26], can control the electromagnetic properties of the superconducting metamaterials. Here we demonstrate the control of electromagnetic properties of the metamaterial by running current through its metallic framework.…”
mentioning
confidence: 99%
“…Nonetheless, RF metamaterials have been sought to improve the performance of magnetic resonance imaging (MRI) devices 6,7 , magnetoinductive lenses 8 , microwave antennas 9 , delay-lines 10 , and resonators 11 . Insofar as obtaining RF metamaterials substantially relies on the development of compact and scalable metamaterial atoms that are amenable to conventional microfabrication techniques, many superconducting structures have been recently introduced and tested for metamaterial applications in the RF/microwave regime [12][13][14][15][16][17][18][19][20][21] , motivated by their low-losses and deep sub-wavelength sizes.…”
mentioning
confidence: 99%